2013
DOI: 10.1039/c3cc39055a
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylated SiO2-coated α-Fe nanoparticles: towards a versatile platform for biomedical applications

Abstract: Carboxylated SiO2-coated α-Fe nanoparticles have been successfully prepared via CaH2-mediated reduction of SiO2-coated Fe3O4 nanoparticles followed by surface carboxylation. These α-Fe-based nanoparticles, which are characterized by ease of coating with additional functional groups, a large magnetization of 154 emu per g-Fe, enhanced corrosion resistivity, excellent aqueous dispersibility, and low cytotoxicity, have potential to be a versatile platform in biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 18 publications
2
31
0
Order By: Relevance
“…Therefore, it is difficult to observe the crystallization of the Fe NPs on SiO 2 . Martinez et al prepared amorphous SiO 2 by a sol-gel procedure and observed in the XRD pattern a broad peak around 2θ = 21.8° corresponding to amorphous SiO 2 [8]. Therefore, the peak at 2θ = 21° may result from the amorphous SiO 2 layer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is difficult to observe the crystallization of the Fe NPs on SiO 2 . Martinez et al prepared amorphous SiO 2 by a sol-gel procedure and observed in the XRD pattern a broad peak around 2θ = 21.8° corresponding to amorphous SiO 2 [8]. Therefore, the peak at 2θ = 21° may result from the amorphous SiO 2 layer.…”
Section: Resultsmentioning
confidence: 99%
“…From the viewpoint of practical applications, any method to fabricate Fe NPs must take into account the susceptibility of Fe NPs to oxidation and aggregation owing to the magnetic interaction between the particles. Controlling the oxidation of Fe NPs is particularly important, as oxidation leads to a degradation in their magnetic properties [3,8]. Since Fe NPs are oxidized rapidly in water and air, they exhibit a loss or decrease in magnetism and dispersibility in a biological environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [18] developed a novel magnetic amino-functionalized Fe 3 O 4 @SiO 2 nanomaterial with a core/shell structure to remove heavy metal ions from aqueous media and found that with amino groups grafted on the silica surface, the nanomaterial showed superior reactivity and high adsorption affinity. Kaori et al [12] have successfully prepared monodispersed Fe@SiO 2 @COOH NPs via CaH 2 -mediated reduction of SiO 2 -coated Fe 3 O 4 nanoparticles followed by modification with COOH-silane. And these particles showed a very high saturation magnetization, enhanced controlled morphology, corrosion resistivity, and low cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The poor hydrophobicity of iron surface is another reason for the lower efficiency of NZVI on removing organic contaminants [1]. So, development of methodologies for the preparation of surface-protected corrosion-resistive NZVI particles has been a key demand [12].…”
Section: Introductionmentioning
confidence: 99%